2016
DOI: 10.5267/j.msl.2016.1.005
|View full text |Cite
|
Sign up to set email alerts
|

Moderating role of entrepreneurial orientation on the relationship between entrepreneurial skills, environmental factors and entrepreneurial intention: A PLS approach

Abstract: For decades, entrepreneurship has become a major concern to both scholars and policymakers because of its significant role in economic and social transformation. This paper modeled the direct effects of entrepreneurial skill, environmental factors and entrepreneurial orientation on entrepreneurial intention as well as the indirect (moderating) effect of entrepreneurial orientation on the relationship of entrepreneurial skill and environmental factors with entrepreneurial intention. Quantitative research design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 55 publications
7
122
0
11
Order By: Relevance
“…Out of those empirical studies most of the studies found that there is a significant and positive relationship exists between EO and SME performance (Hoque & Awang, 2019;Ibrahim, Keat, & AbdulRani, 2017;Ibrahim & Masud, 2016;Al-Dhaafri, Al-Swidi, & Yusoff, 2016;Kantur, 2016). Nevertheless, some of the studies found either not significant Kreiser, Marino, Kuratko, & Weaver, 2013;Hartsfield, Johansen, & Knight, 2008;Naldi, Nordqvist, Sjoberg, & Wiklund, 2007;Slater & Narver, 2000) or mixed relationship between EO and SME performance as the results Tang, Marino, Zhang, & Li, 2008;Walter, Aver, & Ritter, 2006;Swierczek & Ha, 2003;Covina & Slevin, 1989).…”
Section: Entrepreneurial Orientation and Sme Performancementioning
confidence: 99%
“…Out of those empirical studies most of the studies found that there is a significant and positive relationship exists between EO and SME performance (Hoque & Awang, 2019;Ibrahim, Keat, & AbdulRani, 2017;Ibrahim & Masud, 2016;Al-Dhaafri, Al-Swidi, & Yusoff, 2016;Kantur, 2016). Nevertheless, some of the studies found either not significant Kreiser, Marino, Kuratko, & Weaver, 2013;Hartsfield, Johansen, & Knight, 2008;Naldi, Nordqvist, Sjoberg, & Wiklund, 2007;Slater & Narver, 2000) or mixed relationship between EO and SME performance as the results Tang, Marino, Zhang, & Li, 2008;Walter, Aver, & Ritter, 2006;Swierczek & Ha, 2003;Covina & Slevin, 1989).…”
Section: Entrepreneurial Orientation and Sme Performancementioning
confidence: 99%
“…Using EO as a construct that influenced entrepreneurial intention was done by several researchers. For instance, Ibrahim and Lucky (2014) performed a study to determine the relationship between IEO and entrepreneurial intention among Nigerian students in Malaysia and they successfully found that IEO as a single construct was related to students' entrepreneurial intention. In another study, using Norwegian and American students as sample, Robinson and Stubberud (2014) found that students who completed the entrepreneurial course agreed that they were more creative and innovative and demonstrated higher entrepreneurial intent than before.…”
Section: Ieo and Entrepreneurial Intentionmentioning
confidence: 99%
“…Entrepreneurship intention (EI) has been considered a significant construct in the most recent research on entrepreneurship, based on the evidence that EI predicts future entrepreneurial activity even in the long term (Liñán & Fayolle, 2015). Some studies have already related EI to entrepreneurial skills (e.g., Adeyemo, 2009;Ibrahim & Lucky, 2014), taking into account personal characteristics and context factors (e.g., Karimi et al, 2017;Singh, Verma, & Rao, 2016). However, only a few studies have been conducted in health care organisations (e.g., Lages, Marques, Ferreira, & Ferreira, 2016) and specifically involved the growing number of nurses who are part of change processes in different areas of health care activities (e.g., Sankelo & Åkerblad, 2008).…”
Section: Aimsmentioning
confidence: 99%
“…Entrepreneurial skills are necessary basic skills that enable individuals to start and successfully develop a financially viable business (Adeyemo, ). Ibrahim and Lucky () also observed that entrepreneurial skills are an important factor for the development of successful entrepreneurship and that these are related to entrepreneurs' EI.…”
Section: Introductionmentioning
confidence: 97%